Pentasaccharide and Orgaran® Arrest, whereas Heparin Delays Thrombus Formation in a Rat Arteriovenous Shunt - Vogel, Gerard M T; van Amsterdam, Ronald G M; Kop, Wim J; Meuleman, Dirk G (Thrombosis and Haemostasis, 1993)
The mode of action of glycosaminoglycans (GAGs) towards thrombus formation in a rat arteriovenous shunt was studied by simultaneous examination of thrombus weight, platelet consumption and thrombin generation during 45 min of blood circulation. A comparison was made between the effects of heparin, the heparinoid Org 10172 (Orgaran®), and the chemically synthesized methoxy derivative of the antithrombin III binding pentasaccharide fragment of heparin (Org 31540).All three compounds inhibited thrombus growth by 30% at a dose of 80 anti-Xa U/kg i. v. when assessed after 15 min of circulation through the shunt. In addition, a systemic decrease of 27% of platelet numbers in the placebo group was inhibited by heparin and Orgaran® with 63% and by pentasaccharide with 48%. At a later stage, after 45 min of circulation, at comparable plasma anti-Xa levels, thrombi which had formed in the presence of Orgaran® or pentasaccharide, but not in the presence of heparin, became less or non thrombogenic. This non-thrombogenicity was reflected by i) an inhibition of the local deposition of [51Cr]platelets of 75% with Orgaran® and of 57% with pentasaccharide, and ii) an inhibition of ex-vivo thrombus-induced thrombin generation in pooled rat plasma of 67% with Orgaran® and of 52% with pentasaccharide (inhibition compared to placebo).Although the mechanism of inducing non-thrombogenicity of a (developing) thrombus by Orgaran® and pentasaccharide requires further investigation, the suppression of the local thrombin generation potency, measured by thrombus-induced thrombin generation in pooled plasma, is much more correlated with thrombus growth than systemic anticoagulant activity. This suppression is likely to be due to the anti-Xa activity, as reflected by the efficacy of the pure Xa inhibiting pentasaccharide. Limitation of thrombus growth adds to the prophylactic perspective of Orgaran® and pentasaccharide in preventing thrombosis.